Letters of the metropolitan of Kaffa to Moscow in 1542 (a study and publication of texts) - Maksim Moiseev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article makes public the letters from Metropolitan of Kaff a Basilios to Ivan IV, as well as to an unnamed Russian metropolitan. These documents were fi rst brought by the merchant of sultan’s treasury Adrian Greek at the beginning of 1542. He was executing diplomatic duties and, as it seems now, was also the one who presented interests not only of sultan but also of ecumenical patriarch Jeremiah (1521–1545). The importance of these documents is conditioned by the fact that they include the earliest mention of the metropolitan of Kaff a as well as by the fact that they immediately come from the chancellery of this hierarch. The analysis of this document allowed us to make a conclusion about a multifaceted process of forming the complex, the so-called Greek documentation of the Ambassador’s offi ce (Russ. Посольский приказ). It was shown that the first “Greek” Ambassadorial book (посольская книга) is a creation of a later period because the inventories of the Ambassador’s offi ce show a diff erent chronological interval of documents contained in it. Our study points to a more complicated character of selecting and copying charters for the Ambassadorial books. One of the diffi cult issues in the hisotory of making embassy’s registers is the necessity to clarify the reasons why deacons and clerks copied charters of Ottoman sultans and Eastern hierarchs sometimes into “Turkish”, sometimes “Greek” Ambassadorial books. The reasons for the lacuna of 1520?1548 in the 1st “Greek” Ambassadorial book could be connected not only with the factors pointed to by S. M. Kashtanov, but also with the change in the intra-chancellery ideas about belonging of epistles of Eastern Orthodox hierarchs to the documentation of Russian-Turkish relations. The publication of these epistles allows one to broaden the source base for the study of the history of Orthodoxy in the Crimean Peninsula during the Ottoman reign.